Mapping metabolite change in the mouse brain after esketamine injection by ambient mass spectrometry imaging and metabolomics - Liu, Guan-Xi; Li, Ze-Lin; Lin, Su-Yan; Wang, Qian; Luo, Zheng-Yi; Wu, Kai; Zhou, Yan-Lin; Ning, Yu-Ping (Frontiers in Psychiatry, 2023)
Ketamine is a new, fast, and effective antidepression treatment method; however, the possible dissociation effects, sensory changes, abuse risk, and the inability to accurately identify whether patients have a significant response to ketamine limit its clinical use. Further exploration of the antidepressant mechanisms of ketamine will contribute to its safe and practical application. Metabolites, the products of upstream gene expression and protein regulatory networks, play an essential role in various physiological and pathophysiological processes. In traditional metabonomics it is difficult to achieve the spatial localization of metabolites, which limits the further analysis of brain metabonomics by researchers. Here, we used a metabolic network mapping method called ambient air flow-assisted desorption electrospray ionization (AFADESI)-mass spectrometry imaging (MSI). We found the main changes in glycerophospholipid metabolism around the brain and sphingolipid metabolism changed mainly in the globus pallidus, which showed the most significant metabolite change after esketamine injection. The spatial distribution of metabolic changes was evaluated in the whole brain, and the potential mechanism of esketamine’s antidepressant effect was explored in this research.